A scoping review on current technology-based approaches to support breastfeeding and informal human milk exchange practices. - Siti Fatimah Abdul Razak; Nur Liyana Rosli; Noor Hisham Kamis; Norsyamlina Che Abdul Rahim; Mohd Fikri Azli Abdullah (PLoS ONE)
Informal human milk exchange is the practice of donating and receiving expressed human milk based on mutual consent between the donor and receiver in the need of human milk for infants below 2 years old. Main concerns related to informal human milk exchange is related to milk siblings and safety handling of the expressed breastmilk. Even though there are countries which have policies and procedures related to human milk bank, informal milk exchange has not been given much attention. Compared to human milk bank, informal human milk exchange is not regulated. This study aims to identify the system focused on personalized breastfeeding tracking and monitoring, online discussion forum, web-based consultation, and breastfeeding station locator. Review of current applications in supporting breastfeeding practices was conducted based on the PRISMA-ScR framework. A literature search was conducted in Scopus and Google Scholar databases to identify articles published in English or Malay and containing systems/applications related to breastfeeding, milk sharing, milk exchange, milk siblings/kinship within the societal context. According to the scoping review, current scientific publications mostly focused on breast milk, breastfeeding, and milk banking concerns, with recurring themes including social reasons, lactation insufficiency, and unsolved nursing problems. These themes highlight the complexities and complexities of informal human milk exchange practices. Two reviewers screened the articles, and the data were extracted and narratively synthesized. During the primary database search, 360 articles were found based on the related titles, abstracts, and keywords. Seventy eight met the inclusion criteria and were finalized in this review. We found that most scholarly works focused on breast milk, breastfeeding and milk banking challenges and issues with recurrent themes i.e., societies, lactation inadequacy and unresolved nursing problems. Based on our literature search and to the best of our knowledge, there is no recent scoping reviews which focuses on technology-based approaches on informal human milk exchange. Findings from this scoping review is important for advancing research and practice in this field, as well as improving outcomes for individuals and families affected by informal human milk exchange.